(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we examine the maximum outcomes under different strategies of firms. The outcomes suggest that the behavior of the equilibria is not affected by the type of competition. However, when comparing the outcomes, we find that interacting firms in a marketplace to maximize the individual and social outcomes is strongly affected by their positions in a marketplace.